Conflict and dispute reduction mechanism of procurement method for construction industry in Malaysia - Nurul Athirah, Mohd Nasir (2015)
In resolving conflict and dispute for construction industry, various conflict management and dispute resolution methods have been and continue to be explored and develop, but the results are still unsatisfactory in views of tremendous increases of initiation of arbitration and litigation cases. This study examines the extent of innovative procurement method as conflict and dispute reduction mechanism compared to traditional procurement method. The study are divided into two part: Part 1 is concentrated on theory and literature survey, by using texts, journals, conference proceedings, dissertation and computer network information system; Part 2 is field study on issues related to conflict, dispute and procurement methods. One hundred and fifty postal questionnaire has been sent to key players in construction industry such as client, architect, consultant, contractor and quantity surveyor, to collect information, data and views related to conflict, dispute and procurement methods. The survey reveals that the most common used procurement methods, traditional procurement methods had the highest dispute rate comparing to other innovative procurement methods such as Design and Build, Construction Management and Partnering. The survey also reveals that the usage of innovative procurement methods is able to reduce the frequency of dispute occurrence for Malaysia construction industry. For creating a more harmony and peaceful environment in construction industry, appropriate action need to be taken to encourage the industry maximizing the usage of innovative procurement method.